2012
DOI: 10.1128/iai.00678-12
|View full text |Cite
|
Sign up to set email alerts
|

The Hydroxamate Siderophore Rhequichelin Is Required for Virulence of the Pathogenic Actinomycete Rhodococcus equi

Abstract: We previously showed that the facultative intracellular pathogen Rhodococcus equi produces a nondiffusible and catecholatecontaining siderophore (rhequibactin) involved in iron acquisition during saprophytic growth. Here, we provide evidence that the rhbABCDE cluster directs the biosynthesis of a hydroxamate siderophore, rhequichelin, that plays a key role in virulence. The rhbC gene encodes a nonribosomal peptide synthetase that is predicted to produce a tetrapeptide consisting of N 5 -formyl-N 5 -hydroxyorni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
23
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 51 publications
3
23
0
Order By: Relevance
“…The defect in in vitro growth of dual-resistant clinical R. equi isolates was more severe in the absence of iron. R. equi is a facultative intracellular pathogen of host macrophages (20), an environment deprived of iron; to compensate, the bacterium utilizes several mechanisms for iron acquisition (21,22). Due to the low-iron environment in macrophages, it is possible that dual macrolide and rifampin resistance diminishes the ability of R. equi to survive in macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…The defect in in vitro growth of dual-resistant clinical R. equi isolates was more severe in the absence of iron. R. equi is a facultative intracellular pathogen of host macrophages (20), an environment deprived of iron; to compensate, the bacterium utilizes several mechanisms for iron acquisition (21,22). Due to the low-iron environment in macrophages, it is possible that dual macrolide and rifampin resistance diminishes the ability of R. equi to survive in macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…Given the essential role of iron in bacterial metabolism, and considering the very low amounts of free iron in the mammalian host, it is not surprising that, in different bacterial pathogens, mutations in specific iron-uptake mechanisms have been found to dramatically reduce the ability to cause infection in a variety of animal models [65][66][67][68][69][70][71]. Consequently, inhibition of iron uptake or disruption of bacterial iron metabolism has been proposed as a promising target for the development of new antibacterial drugs [72][73][74][75].…”
Section: The Rationale Of Targeting Bacterial Iron Metabolismmentioning
confidence: 99%
“…In addition to the plasmid-encoded virulence factors, a number of virulence-associated factors, including cytoadhesive pili (24), the hydroxamate siderophore rhequichelin (25), and isocitrate lyase (26), are encoded by the chromosome. Comparative genome analysis demonstrated that many of these have orthologues in nonpathogenic actinobacteria.…”
mentioning
confidence: 99%